1996
DOI: 10.1002/j.1460-2075.1996.tb00354.x
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of the peptide binding site of the human galanin receptor.

Abstract: Galanin, a neuroendocrine peptide of 29 amino acids, binds to Gi/Go‐coupled receptors to trigger cellular responses. To determine which amino acids of the recently cloned seven‐transmembrane domain‐type human galanin receptor are involved in the high‐affinity binding of the endogenous peptide ligand, we performed a mutagenesis study. Mutation of the His264 or His267 of transmembrane domain VI to alanine, or of Phe282 of transmembrane domain VII to glycine, results in an apparent loss of galanin binding. The su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 37 publications
3
40
1
Order By: Relevance
“…Under conditions where significant interactions of Rh-CP were observed with FCS, only marginal effects were found in the radioligand assay. This result is in contrast to a similar study with galanin in which the interaction of the Rh-labeled ligand with its membrane-bound receptor was studied (29) and could be compared with radioligand binding in cells overexpressing the galanin receptor (35). It is concluded that the receptor density present in the cells used in our study is sufficient for successful FCS analysis but not for radioligand studies.…”
contrasting
confidence: 53%
“…Under conditions where significant interactions of Rh-CP were observed with FCS, only marginal effects were found in the radioligand assay. This result is in contrast to a similar study with galanin in which the interaction of the Rh-labeled ligand with its membrane-bound receptor was studied (29) and could be compared with radioligand binding in cells overexpressing the galanin receptor (35). It is concluded that the receptor density present in the cells used in our study is sufficient for successful FCS analysis but not for radioligand studies.…”
contrasting
confidence: 53%
“…Identification of receptor residues that are involved in ligand binding is a fundamental step in elucidating and understanding the principles of ligand-receptor interactions. Such studies have been performed on GalR1 and GalR2, delineating both conserved and subtype different interaction with galanin receptor ligands (Kask et al, 1996;Berthold et al, 1997;Kask et al, 1998;Church et al, 2002;Lundströ m et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Site-directed mutagenesis studies have been performed on both hGalR1 and hGalR2 to map the binding pocket (Kask et al, 1996;Berthold et al, 1997;Kask et al, 1998;Lundströ m et al, 2007), and a three-dimensional model of hGalR1 has been presented by Iismaa and co-workers (Church et al, 2002). Altogether these reports indicate that TM helices III, VI and VII together with extracellular loop (ECL) II and III form the binding pocket of Galanin is a neuropeptide found throughout the central and peripheral nervous systems of a wide range of species, ranging from human and mouse to frog and tuna.…”
Section: Introductionmentioning
confidence: 99%
“…The low receptor density made the use of the relatively crude radioligand assays difficult, a situation which can be compared with that of the galanin receptor. Overexpression of the galanin receptor made it possible to show high-affinity binding sites by a conventional method in addition to the use of FCS [28].…”
Section: Discussionmentioning
confidence: 99%